Application of Prussian blue staining in the diagnosis of ocular siderosis - Zhen Yang; Xiao-Li Yang; Li-Shuai Xu; Le Dai; Mei-Chao Yi (International Journal of Ophthalmology, 2014)
AIM:To explore the value of Prussian blue staining in the diagnosis of ocular siderosis.METHODS: Between January 2012 and January 2013, the Prussian blue stain used in anterior lens capsule and vitreous liquid after centrifugation from patients with definitive diagnosis and suspicious diagnosed of ocular siderosis. At the same time, give a negative control.RESULTS: Anterior lens capsule membrane and liquid of vitreous cavity from patients with definitive diagnosis and suspicious diagnosed of ocular siderosis revealed ferric ions that stained positively with Prussian blue. In the control group, there is no positive reaction.CONCLUSION: Prussian blue staining in the diagnosis of ocular siderosis has a very significant worth, suspected cases can be definitive diagnosed.